2013
DOI: 10.1021/am403702n
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin-Enhanced Extraction and Energy Transfer of Carcinogens in Complex Oil Environments

Abstract: Reported herein is the use of γ-cyclodextrin for two tandem functions: (a) the extraction of carcinogenic polycyclic aromatic hydrocarbons (PAHs) from oil samples into aqueous solution, and (b) the promotion of highly efficient energy transfer from the newly extracted PAHs to a high-quantum yield fluorophore. The extraction proceeded in moderate to good efficiencies, and the resulting cyclodextrin-promoted energy transfer lead to a new, brightly fluorescent signal in the aqueous solution. The resulting dual-fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 48 publications
(74 reference statements)
0
18
0
Order By: Relevance
“…We demonstrated that this toxicant detection system operates in a broad range of environments, including plasma, 32 breast milk, 33 and urine, 34 as well as in extracts collected in the aftermath of the 2010 Deepwater Horizon oil spill. 35 Although our previous work detected polycyclic aromatic hydrocarbons, 36 polychlorinated biphenyls, 37 aromatic amines, pesticides, 38 aliphatic alcohols, and fuel spill components, we have not used cyclodextrin systems for the detection of BPA and BPA derivatives to date.…”
Section: Fig 1 Schematic Of Cyclodextrin-promoted (A) Energy Transfementioning
confidence: 95%
“…We demonstrated that this toxicant detection system operates in a broad range of environments, including plasma, 32 breast milk, 33 and urine, 34 as well as in extracts collected in the aftermath of the 2010 Deepwater Horizon oil spill. 35 Although our previous work detected polycyclic aromatic hydrocarbons, 36 polychlorinated biphenyls, 37 aromatic amines, pesticides, 38 aliphatic alcohols, and fuel spill components, we have not used cyclodextrin systems for the detection of BPA and BPA derivatives to date.…”
Section: Fig 1 Schematic Of Cyclodextrin-promoted (A) Energy Transfementioning
confidence: 95%
“…We have previously reported a fundamentally new approach for toxicant detection and potential environmental remediation: the use of commercially available, non-toxic cyclodextrin derivatives for the efficient extraction of PAHs from oils, and for their subsequent detection via proximity-induced energy transfer [8]. This system operates successfully to extract PAHs from motor oil, vacuum pump oil, and vegetable oil, as well as from oil collected from oil spill sites and from tar balls [9].…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] We have developed a new approach for the cleanup of oil spills in marine environments that focuses on the removal of aromatic toxicants such as polycyclic aromatic hydrocarbons (PAHs). 16 The removal of PAHs is particularly important because many of these compounds are known carcinogens or pro-carcinogens, 17 including the Class I carcinogen benzo[a]pyrene (Chart 1, compound 3). 18 This approach uses commercially available, non-toxic γ -cyclodextrin to bind…”
mentioning
confidence: 99%